2016
DOI: 10.1186/s12890-016-0173-9
|View full text |Cite
|
Sign up to set email alerts
|

Association between personal exposure to ambient metals and respiratory disease in Italian adolescents: a cross-sectional study

Abstract: Background: Release of ambient metals during ferroalloy production may be an important source of environmental exposure for nearby communities and exposure to these metals has been linked to adverse respiratory outcomes. We sought to characterize the association between personal air levels of metals and respiratory health in Italian adolescents living in communities with historic and current ferroalloy activity. Methods: As part of a study in the industrial province of Brescia, Italy, 410 adolescents aged 11-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The assessment of air-Mn in order to evaluate the influence of air pollution on human Mn exposure and the related health implications is of relevant and growing interest. Previous Italian studies, which assessed levels of PM 10 air-Mn using a 24-h personal sampling, reported deficits in olfactory and motor neuron function in the higher exposed group of both elderly (57) and adolescents (58), as well an increased risk of asthma only in the youngest population (35). More recently, in the absence of facility emissions data for individual study subjects, a US study used the long-term air measurements available from local air monitoring stations in order to derive receptor-specific concentrations of respirable air Mn through total suspended particulates (TSP), PM 10 and PM 2.5 (59).…”
Section: Discussionmentioning
confidence: 99%
“…The assessment of air-Mn in order to evaluate the influence of air pollution on human Mn exposure and the related health implications is of relevant and growing interest. Previous Italian studies, which assessed levels of PM 10 air-Mn using a 24-h personal sampling, reported deficits in olfactory and motor neuron function in the higher exposed group of both elderly (57) and adolescents (58), as well an increased risk of asthma only in the youngest population (35). More recently, in the absence of facility emissions data for individual study subjects, a US study used the long-term air measurements available from local air monitoring stations in order to derive receptor-specific concentrations of respirable air Mn through total suspended particulates (TSP), PM 10 and PM 2.5 (59).…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary function indices and asthma in children were linked with Pb [ 27 , 28 ], Mn, Ni, and Cr [ 29 , 30 ], as well as Co and Zn [ 31 ]. Likewise, maternal Pb has been reported in association with elevated blood pressure in 5-year-old children [ 32 ] and prenatal exposure to Cd—with an increased risk of obesity at the age of five [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies observed that asthma induced by heavy metals was triggered by the immune system, indicating that heavy metals have great inflammatory potential and immunomodulatory effects on individuals [ 27 , 28 ]. Many studies have reported the association between heavy metals (Pb, Cd, Hg and Mn) and asthma [ 24 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%